Study of the cwaRS-ldcA Operon Coding a Two-Component System and a Putative L,D-Carboxypeptidase in Lactobacillus paracasei - Scornec, Hélène; Palud, Aurore; Pédron, Thierry; Wheeler, Richard; Petitgonnet, Clément; Boneca, Ivo Gomperts; Cavin, Jean-François; Sansonetti, Philippe J.; Licandro, Hélène (Frontiers in Microbiology, 2020)
The cell surface is the primary recognition site between the bacterium and the host. An operon of three genes, LSEI_0219 (cwaR), LSEI_0220 (cwaS) and LSEI_0221 (ldcA) has been previously identified as required for the establishment of L. paracasei in the gut. The genes cwaR and cwaS encode a predicted two-component system (TCS) and ldcA a predicted D-Alanyl-D-Alanine carboxypeptidase that is a peptidoglycan biosynthesis enzyme. We explored the functionality and the physiological role of these three genes, particularly their impact on the bacterial cell wall architecture and on the bacterial adaptation to environmental perturbations in the gut. The functionality of CwaS/R proteins as a TCS has been demonstrated by biochemical analysis. It is involved in the transcriptional regulation of several genes of the peptidoglycan biosynthesis. Analysis of the muropeptides of peptidoglycan in mutants allowed us to re-annotate LSEI_0221 as a putative L,D-carboxypeptidase (LdcA). The absence of this protein coincided with a decrease of two surface antigens: LSEI_0020, corresponding to p40 or msp2 whose implication in the host epithelial homeostasis has been recently studied, and LSEI_2029 which has never been functionally characterized. The inactivation of each of these three genes induces susceptibility to antimicrobial peptides (hBD1, hBD2 and CCL20), which could be the main cause of the gut establishment deficiency. Thus, this operon is necessary for the presence of two surface antigens and for a suitable cell wall architecture.